Stiffness characteristics of the lower extremities in Women’s Chinese Basketball Association competition athletes: normative values and position differences - Wang, Dan; Wang, Zhihai; Yang, Mingming; Qu, Kaiyuan; Mao, Xinyu; Yang, Xin; Zhang, Zhiye; Shao, Che; Delahunt, Eamonn; Fang, Wenxuan (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeHigher stiffenss is expected to augment performance by increasing the utilisation of elastic energy. However, excessive lower extremity stiffness increases the risk of bony injuries; while insufficient stiffness is associated with a higher likelihood of soft tissue injuries. Thus, there might be an ‘optimal’ stiffness value or range that allows for maximising athletic performance while simultaneously minimising risk of sports injury. Basketball players can be classified by position as centres, guards and forwards, with each position characterised by specific injury risks and exercise patterns. Therefore, this study aims to establish normative data for lower extremity stiffness characteristics of players in the Women’s Chinese Basketball Association (WCBA) and compare the characteristics based on position.MethodsA total of 124 WCBA athletes (over 70% of the WCBA teams) were recruited for this study, including 63 forwards, 22 centres and 39 guards. Stiffness was evaluated before and during the 2020–2021 WCBA season, which was averaged for data analysis. Quasi-static stiffness measurements of muscles and tendons were collected via a handheld myometer on seven sites of each leg. Vertical stiffness was also evaluated by OptoGait system.ResultsDescriptive statistics were used to establish the normative values of stiffness for forwards, centres and guards. The Kruskal Wallis test and post hoc Bonferroni pairwise comparisons found significant higher stiffness of the left patellar tendon (PT) in guards than centres (p = 0.004) and in guards than forwards (p = 0.012), right PT stiffness in guards than centres (p = 0.016) and in guards than forwards (p = 0.017), mean PT stiffness in guards than centres (p = 0.003) and in guards than forwards (p = 0.008); stiffness of the right soleus (SOL) in guards than forwards (p = 0.033), stiffness of the left biceps femoris (BF) in forwards than centres (p = 0.049) and in guards than centres (p = 0.038); and stiffness of the left vertical stiffness (hopping) in forwards than centres (p = 0.041).ConclusionForwards, centres and guards were characterised by significantly different stiffness values, which could be utilised for improvement of athletic performance and injury prevention.